FACTORS AND PRINCIPLES OF FORMATION OF LEGAL CULTURE OF DISABLED PRIMARY STUDENTS - Abdullaev Bakhodirjon Mahamadjonovich (Web of Journals Publishing, 2023)
This article describes the current issues of forming the legal culture of children with disabilities, the requirements and principles for the process of forming legal culture in educational activities.
Keywords: children with disabilities, deaf and hard of hearing children, special boarding school, educational training, teacher, educator, state, law, society, democracy, legal order, law, humanity, freedoms, justice, humanitarianism, legal culture.